ASSISTED BREECH DELIVERY WITH TRANSVERSE VAGINAL SEPTUM - Anwar, Sadia; Moon, Tooba; Baloch, Sajjad Ahmad; Shah, Syed Humayun (Journal of Ayub Medical College Abbottabad, 2012)
The incidence of vaginal septum is rare. The infrequency of this anomaly makes accurate estimates of the true incidence very difficult to obtain. Diagnosis is based on careful history and examination. This is the case of a patient who presented with transverse vaginal septum in labour and breech presentation. The septum was resected and the foetus delivered normally. Careful vaginal examination should be performed in pregnant women at term before labour to detect such manageable abnormalities.